2021
DOI: 10.3389/fimmu.2020.603039
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Induced Complement Activation: Implications for Cancer Nanomedicine

Abstract: Nanoparticle-based anticancer medications were first approved for cancer treatment almost 2 decades ago. Patients benefit from these approaches because of the targeted-drug delivery and reduced toxicity, however, like other therapies, adverse reactions often limit their use. These reactions are linked to the interactions of nanoparticles with the immune system, including the activation of complement. This activation can cause well-characterized acute inflammatory reactions mediated by complement effectors. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 139 publications
(181 reference statements)
1
24
0
Order By: Relevance
“…In a third assay, the "VBP + CBP"decorated nanoparticles (t-LNPs) were evaluated via ELISA for their ability to activate complement C3 to C3a, as this would indicate a systemic complement-mediated immunological risk. 63 As is shown is Figure 3C, the C3a/C3 ratio in plasma remained similar to the baseline (saline), on incubation with control nanoparticles or t-LNPs, indicating that in vivo these particles would have minimal complement activation risks. In a fourth assay, the control particles as well as t-LNPs were evaluated for their ability to activate neutrophils, because this would indicate an unwanted stimulation of the innate immune defense mechanism.…”
Section: Resultssupporting
confidence: 59%
“…In a third assay, the "VBP + CBP"decorated nanoparticles (t-LNPs) were evaluated via ELISA for their ability to activate complement C3 to C3a, as this would indicate a systemic complement-mediated immunological risk. 63 As is shown is Figure 3C, the C3a/C3 ratio in plasma remained similar to the baseline (saline), on incubation with control nanoparticles or t-LNPs, indicating that in vivo these particles would have minimal complement activation risks. In a fourth assay, the control particles as well as t-LNPs were evaluated for their ability to activate neutrophils, because this would indicate an unwanted stimulation of the innate immune defense mechanism.…”
Section: Resultssupporting
confidence: 59%
“…enhance the intracellular uptake (Figure 1e,f; Figures S7,S8, Supporting Information). According to the intracellular trafficking of EVs, [26][27][28][29] HRED and ED entered into lysosomes or cytoplasm after they internalized into cells, thus some of DOX from HRED or ED was degraded in lysosomes, and other DOX was released into the cytoplasm. Laser confocal microscopy images of ED and HRED in SKOV3/DOX and SKOV3 cells also showed that EVs or HRE (PKH67 labeled, green fluorescence) located in cytoplasm and red signal of DOX mainly distributed in nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Although sometimes beneficial in prophylactic protection, uncontrolled complement activation is harmful and contributes to disease progression . In cancer therapeutics, complement activation by nanoparticles has several implications and gold nanoparticles are also known to interact with the complement system. To be used as an immunotherapeutic these glyconanoparticles must not induce complement-mediated anaphylaxis. Thus, we sought to study the effect of the mannosylated glycogold nanoparticles of the complement system.…”
Section: Resultsmentioning
confidence: 99%